2015
DOI: 10.1071/ch15461
|View full text |Cite
|
Sign up to set email alerts
|

The Synthesis and Biological Evaluation of Anithiactin A/Thiasporine C and Analogues

Abstract: The synthesis of anithiactin A has been achieved in four steps. Several closely related analogues were synthesised and their biological activity against colon and breast cancer cell lines evaluated. Anithiactin A was found not to be cytotoxic even at a high concentration (100 μM); however, two 4-substituted phenyl thiazoles were found to be moderately cytotoxic at 10 μM. Based on these results, 4-substitution on the phenyl group appears to be critical for cytotoxicity. However, the exact electronic and structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Its structure was assigned to contain a 5-hydroxy-4 H -1,3-thiazin-4-one moiety which was the first example of such a ring system in a natural product. Motivated by the unusual heterocycle and its activity against the nonsmall-cell lung cancer cell line H2122 (IC 50 5.4 μM), , the Christmann laboratory completed a synthesis of 5-hydroxy-4 H -1,3-thiazin-4-ones from arylthioamides. Comparison of the 1 H and 13 C NMR spectra for isolated thiasporine A and synthetic 1a indicated a problem with its structural assignment.…”
mentioning
confidence: 99%
“…Its structure was assigned to contain a 5-hydroxy-4 H -1,3-thiazin-4-one moiety which was the first example of such a ring system in a natural product. Motivated by the unusual heterocycle and its activity against the nonsmall-cell lung cancer cell line H2122 (IC 50 5.4 μM), , the Christmann laboratory completed a synthesis of 5-hydroxy-4 H -1,3-thiazin-4-ones from arylthioamides. Comparison of the 1 H and 13 C NMR spectra for isolated thiasporine A and synthetic 1a indicated a problem with its structural assignment.…”
mentioning
confidence: 99%
“…Shortly thereafter, a marine-derived bacterium, Actinomycetospora sp., has also produced anithiactins A and C along with thiasporine A [7,8]. Several studies regarding the synthesis of these secondary metabolites have been reported [6,[9][10][11]. Intensive investigation of the chemical components of the culture broth of the strain 10A085 has led to the isolation of a new 2-phenylthiazole natural product, anithiactin D (1).…”
Section: Introductionmentioning
confidence: 99%
“…substrates for olefin metathesis, [5] exploration of the catalytic reactivity of nickel phosphine-phosphite complexes, [6] studies towards the synthesis of microspinosamide [7] and the roseophilins, [8] the synthesis of anithiactin A [9] and atropisomeric dibenzo[1,3]diazepines, [10] observation of an unexpected isomerisation process during fragment-based screening of HIV integrase, [11] the study of steric and electronic effects in the synthesis and hydrolysis of imides, [12] studies of photoswitchable carbohydrate fluorosurfactants, [13] the rapid microwaveassisted synthesis of N-aryl tetrahydroisoquinolines, [14] and the development of thiol-reactive drug analogues to probe receptor binding. [15] Finally, two highlight articles describe recent applications of rhodium(II) azavinyl carbenes [16] and Brønsted acidmediated radical processes [17] in organic synthesis.…”
mentioning
confidence: 99%